Dorycranosus pulcher sp. n. (Oribatei, Liacaridae) — новый вид панцирного клеща - Сергиенко, Г.Д.; Джапаридзе, Н.И. (Вестник зоологии, 1981)
A description is presented for Dorycranosus pulcher Sergienko et Djaparidze, a new species of beetle mites from a nest or Clernronomys glareous Schreb. The species is compared with a closely related species D. columbianus (Berlese , 1908).